The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5853/jos.2014.16.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Attitudes Toward Guidelines for Stroke: A Survey of Korean Neurologists

Abstract: Background and PurposeClinical practice guidelines (CPGs) are regarded as an essential guidance tool for practicing physicians. We surveyed physicians in Korea in order to evaluate their attitudes toward the Korean CPGs for stroke.MethodsWe obtained participation agreement for our survey from 27 centers of the 33 most actively contributing to the Korean Stroke Registry. A total of 174 neurologists participated in a questionnaire interview regarding their attitudes toward CPGs for stroke.ResultsOf 174 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our study on palliative care professionals shows an overall similar dominance of positive attitudes and beliefs concerning guidelines compared to results found in other studies outside palliative care [ 14 , 16 29 ], which focus on physicians [ 14 , 16 18 , 23 , 25 32 ], nurses [ 21 , 22 ] or both [ 19 , 20 , 24 ]. We did not find any data published for palliative care professionals’ attitudes towards guidelines in general.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our study on palliative care professionals shows an overall similar dominance of positive attitudes and beliefs concerning guidelines compared to results found in other studies outside palliative care [ 14 , 16 29 ], which focus on physicians [ 14 , 16 18 , 23 , 25 32 ], nurses [ 21 , 22 ] or both [ 19 , 20 , 24 ]. We did not find any data published for palliative care professionals’ attitudes towards guidelines in general.…”
Section: Discussionsupporting
confidence: 83%
“…Forty-one percent had general problems in the application of guidelines, the main specific doubt was the difficulty to change already existing routine treatments (57%). Other doubts regarding practical aspects of guideline implementation were not assessed, but lack of time and medical resources were reported by others [ 23 , 25 , 29 ]. In an online survey from Estonia, Taba et al [ 29 ] showed that time was the barrier identified by most physicians (42%), followed by lack of medical resources for implementation (32%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey conducted in 2011, Korean neurologists were reported to support (ie, had positive attitudes at a frequency of 85%) toward the use of the national guidelines, and >60% of the physicians reported adherence to the Korean stroke guideline in dyslipidemia management for the secondary prevention of stroke. 33 We speculate that the spread and implementation of the stroke CPG in our national language may have improved physician adherence to the guidelines. 13,33 Limitations of this study are acknowledged.…”
Section: Discussionmentioning
confidence: 93%
“…33 We speculate that the spread and implementation of the stroke CPG in our national language may have improved physician adherence to the guidelines. 13,33 Limitations of this study are acknowledged. First, this is a multicenter study of 12 university hospitals or regional stroke centers in Korea, and thus, generalizability of the study results may be limited.…”
Section: Discussionmentioning
confidence: 93%